Cultural Transfers in Education between Italy and Swiss Canton Tessin (1894-1936) - Sahlfeld, Wolfgang (Swiss Journal of Educational Research, 2018)
In the period 1880-1940 the education system of italian-speaking Canton Ticino was seeing pedagogical transfers coming from Italy. In a first period, the peagogical élite although deied that these pedagocal ideas came from Italy, using the terminological (and ideological) construction of “Metodo intuitivo” (i.e. Pestalozzi and Girard as the only fathers of the method). After 1910 the pedagogical influence of italian New Education (Montessori, Lombardo-Radice) grew more because the general interest in Ticino for italian culture grew with the movement for Defence of Ticino’s italian identity. World war 1 and fascism brought the New Education fellows in Ticino into a deep dilemma: their pedagogical ideas and actions were accepted only if accompanied by a total distance from any official italian political position. This was very difficult and led at the end to a growing total distance from Italy, even if the pedagogical élite tried to avoid the complete end of any cultural contact with Italy. The end cames with Abyssinia war and World war II that led to a total isolation of Ticino from Italy.